Ghrelin‐mediated improvements in the metabolic phenotype in the R6/2 mouse model of Huntington's disease. (8th April 2019) - Rudenko, Olga; Springer, Cecilie; Skov, Louisa J.; Madsen, Andreas N.; Hasholt, Lis; Nørremølle, Anne; Holst, Birgitte
Abstract: Huntington's disease (HD) is a heritable neurodegenerative disorder, characterised by metabolic disturbances, along with cognitive and psychiatric impairments. Targeting metabolic HD dysfunction via the maintenance of body weight and fat mass and restoration of peripheral energy metabolism can improve the progression of neurological symptoms. In this respect, we focused on the therapeutic potential of the orexigenic peptide hormone ghrelin, which plays an important role in promoting a positive energy balance. In the present study, we found a significant disruption of circadian metabolic regulation in a R6/2 mouse HD model in the late stage of disease. Daily circadian rhythms of activity, energy expenditure, respiratory exchange ratio and feeding were strongly attenuated in R6/2 mice. During the rest phase, R6/2 mice had a higher total activity, elevated energy expenditure and excessive water consumption compared to control mice. We also found that, in the late stage of disease, R6/2 mice had ghrelin axis deficiency as a result of low circulating ghrelin levels, in addition to down‐regulation of the ghrelin receptor and several key signalling molecules in the hypothalamus, as well as a reduced responsiveness to exogenous peripheral ghrelin. We demonstrated that, in pre‐symptomatic mice, responsiveness to ghrelin is preserved. Chronic ghrelin treatment efficiently increased lean body mass and decreased the energy expenditure and fat utilisation of R6/2 mice in the early stage of disease. In addition, ghrelin treatment was also effective in the normalisation of drinking behaviour and the rest activity of these mice. Ghrelin treatment could provide a novel therapeutic possibility for delaying disease progression; however, deficiency in ghrelin receptor expression could limit its therapeutic potential in the late stage of disease.